Biobased Transesterification Vitrimers - Kumar, Ashwani; Connal, Luke A. (Macromolecular rapid communications., 2023)
The rapid increase in the use of plastics and the related sustainability issues, including the depletion of global petroleum reserves, have rightly sparked interest in the use of biobased polymer feedstocks. Thermosets cannot be remolded, processed, or recycled, and hence cannot be reused because of their permanent molecular architecture. Vitrimers have emerged as a novel polymer family capable of bridging the difference between thermoplastic and thermosets. Vitrimers enable unique recycling strategies, however, it is still important to understand where the raw material feedstocks originate from. Transesterification vitrimers derived from renewable resources are a massive opportunity, however, limited research has been conducted in this specific family of vitrimers. This review article provides a comprehensive overview of transesterification vitrimers produced from biobased monomers. The focus is on the biomass structural suitability with dynamic covalent chemistry, as well as the viability of the synthetic methods. Biobased vitrimers can provide a sustainable approach to replace fossil fuel‐derived thermoset plastics. This review presents a comprehensive overview of the design, synthesis, and dynamic properties of biobased vitrimeric materials with a focus on the transesterification bond exchange process. Future plans and difficulties for the development of biobased transesterification vitrimers with excellent performance are also presented.